Two-eyed seeing of the integration of oral health in primary health care in Indigenous populations: a scoping review - Richa Shrivastava; Yves Couturier; Felix Girard; Lucie Papineau; Elham Emami (International Journal for Equity in Health, 2020)
Abstract Background Indigenous people experience significant poor oral health outcomes and poorer access to oral health care in comparison to the general population. The integration of oral health care with primary health care has been highlighted to be effective in addressing these oral health disparities. Scoping studies are an increasingly popular approach to reviewing health research evidence. Two-eyed seeing is an approach for both Western and Indigenous knowledge to come together to aid understanding and solve problems. Thus, the two-eyed seeing theoretical framework advocates viewing the world with one eye focused on Indigenous knowledge and the other eye on Western knowledge. This scoping review was conducted to systematically map the available integrated primary oral health care programs and their outcomes in these communities using the two-eyed seeing concept. Methods This scoping review followed Arksey and O’Malley’s five-stage framework and its methodological advancement by Levac et al. A literature search with defined eligibility criteria was performed via several electronic databases, non-indexed Indigenous journals, Indigenous health organizational websites, and grey literature. The charted data was classified, analyzed, and reported using numeral summary and qualitative content analysis. The two-eyed seeing concept guided the interpretation and synthesis of the evidence on approaches and outcomes. Results A total of 29 publications describing 30 programs conducted in Australia and North America from 1972 to 2019 were included in the final analysis. The following four program categories emerged from the analysis: oral health promotion and prevention programs (n = 13), comprehensive dental services (n = 13), fly in, fly out dental services (n = 3), and teledentistry (n = 1). Biomedical approaches for integrated primary oral health care were leadership and governance, administration and funding, capacity building, infrastructure and technology, team work, and evidence-based practice. Indigenous approaches included the vision for holistic health, culturally appropriate services, community engagement, shared responsibility, and cultural safety. The program outcomes were identified for biological, mental, and emotional dimensions of oral health; however, measurement of the spiritual dimension was missing. Conclusion Our results suggest that a multiple integrated primary oral health care approach with a particular focus on Indigenous culture seems to be efficient and relevant in improving Indigenous oral health.